2016
DOI: 10.1186/s12906-016-1228-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tangshen Formula on urinary and plasma liver-type fatty acid binding protein levels in patients with type 2 diabetic kidney disease: post-hoc findings from a multi-center, randomized, double-blind, placebo-controlled trial investigating the efficacy and safety of Tangshen Formula in patients with type 2 diabetic kidney disease

Abstract: BackgroundTangshen Formula (TSF) is a traditional Chinese medicine for the treatment of diabetic kidney disease (DKD). Liver-type fatty acid binding protein (L-FABP) is expressed in various tissues, including the kidney, where it is known as urinary L-FABP. Other studies demonstrated that urinary L-FABP may be a useful biomarker for monitoring DKD. This post-hoc analysis and cross-sectional study evaluated the changes in urinary L-FABP in DKD patients treated with TSF and conventional medicine.MethodsPost-hoc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
(45 reference statements)
0
25
0
1
Order By: Relevance
“…Multiple clinical studies by Ping Li’s research group have demonstrated the efficacy of the Tangshen formula in attenuating diabetic kidney disease in rodent models and human patients [25]. Notably, a 2015 multicenter RCT in type 2 diabetic patients with diabetic kidney disease has also revealed that the Tangshen formula produces a significant decrease in 24-hour urinary protein as well as significant improvements in the estimated glomerular filtration rate (eGFR) relative to placebo [26].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical studies by Ping Li’s research group have demonstrated the efficacy of the Tangshen formula in attenuating diabetic kidney disease in rodent models and human patients [25]. Notably, a 2015 multicenter RCT in type 2 diabetic patients with diabetic kidney disease has also revealed that the Tangshen formula produces a significant decrease in 24-hour urinary protein as well as significant improvements in the estimated glomerular filtration rate (eGFR) relative to placebo [26].…”
Section: Discussionmentioning
confidence: 99%
“…According to the traditional Chinese medicine theory of Professor Kefu Chai, it is believed that the basic pathogenesis of early-and medium-stage DN is the deficiency of both Qi and Yin, which results in blood stasis (15). Previous results have indicated that a Chinese herbal compound prescription, Tangshen (TS) formula, has demonstrated good clinical efficacy in managing early-stage DN, as it is believed in traditional Chinese medicine that it supplements Qi, nourishes Yin, improves blood flow and removes obstructions in the blood vessels (16). In the present study, the molecular mechanisms of TS formula in a DN rat model were analyzed, providing a deeper insight into the effects of TS formula in the treatment of DN.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] Qigong can also improve cognitive function in the early stages of dementia, 12 whereas TCM decoctions can be used as adjuvant treatment for patients with stroke and chronic obstructive pulmonary disease, chronic liver disease, chronic heart failure, and chronic or type 2 diabetic kidney disease. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] Second, TCM can improve symptoms. For example, acupuncture and Chinese herbal medicines are recommended for cancer pain and serve to reduce opioid abuse.…”
Section: Suggestionsmentioning
confidence: 99%